A Lithium‐Sulfur Battery with a High Areal Energy Density. (23rd June 2014) - Kim, Joo‐Seong; Hwang, Tae Hoon; Kim, Byung Gon; Min, Jaeyun; Choi, Jang Wook
<x xml:space="preserve">Abstract</x> The battery community has recently witnessed a considerable progress in the cycle lives of lithium‐sulfur (Li‐S) batteries, mostly by developing the electrode structures that mitigate fatal dissolution of lithium polysulfides. Nonetheless, most of the previous successful demonstrations have been based on limited areal capacities. For realistic battery applications, however, the chronic issues from both the anode (lithium dendrite growth) and the cathode (lithium polysulfide dissolution) need to be readdressed under much higher loading of sulfur active material. To this end, the current study integrates the following three approaches in a systematic manner: 1) the sulfur electrode material with diminished lithium polysulfide dissolution by the covalently bonded sulfur‐carbon microstructure, 2) mussel‐inspired polydopamine coating onto the separator that suppresses lithium dendrite growth by wet‐adhesion between the separator and Li metal, and 3) addition of cesium ions (Cs+) to the electrolyte to repel incoming Li ions and thus prevent Li dendrite growth. This combined strategy resolves the long‐standing problems from both electrodes even under the very large sulfur‐carbon composite loading of 17 mg cm−2 in the sulfur electrode, enabling the highest areal capacity (9 mAh cm−2) to date while preserving stable cycling performance.